The Minimalism and Contentment in Chloé Zhao Nomadland - Wildan Chaniago; Irdina Ariana; Yanti Rosalinah (English Education and Literature Journal (E-Jou), 2026)
This study analyzes the representation of minimalism and contentment in Chloé Zhao’s film Nomadland (2020) by applying a qualitative descriptive method supported by textual film analysis. The research focuses on how the film’s dialogue, scene, and overall atmosphere construct a coherent depiction of a minimalist lifestyle and an inner sense of contentment. The findings indicate that Nomadland presents minimalism as a deliberate lifestyle choice and contentment in the film emerges from acceptance, gratitude, and the ability to find peace within life’s uncertainties and limitations. This study concludes that Nomadland successfully integrates the values of minimalism and contentment into its artistic and thematic design, illustrating how simplicity, acceptance, and emotional balance can guide individuals toward a deeper understanding of meaning and well-being in contemporary life